THE EFFECT OF A PRINTED EXTENSIVE READING INSTRUCTIONAL PROGRAM ON JORDANIAN SECONDARY STAGE STUDENTS’ PROFICIENCY IN ENGLISH - Smadi, Oqlah; Al-Zawahreh, Ahmad (European Scientific Journal, ESJ, 2013)
This paper reports the findings of a study that examined the effect of a Printed Extensive Reading (henceforth, PER) instructional program on Jordanian Eleventh grade students’ proficiency in English and detected their opinions towards the effectiveness of the instructional program on their proficiency. In this study, the researchers utilized a cyclical integrative model through which the focus was paid to input and output skills evenly and simultaneously, quantitative and qualitative research instruments to ensure the credibility of the results, simplified and authentic ER material selected by the researcher in light of a set of criteria as will be shown in the methodology section and examined the target students’ proficiency as a whole. To collect the data, a sample of two intact Eleventh grade sections from King Abdullah the Second School for Excellence was selected; one section was assigned to be the experimental group, the other as a control group. The quantitative findings of the study revealed that the mean scores of the experimental group were significantly higher than the mean scores of the control group, particularly in writing, speaking, vocabulary, reading comprehension and listening due to the teaching methodology. The findings of the study did not reveal any significant difference in the students’ grammar proficiency. Further, the results of the questionnaire revealed that the respondents were appreciative and pleased with the effectiveness of the PER program. This result was also supported by the qualitative findings of the interview.